History and anthology of homosexuality = Histoire et anthologie de l'homosexualité. - Chardans, Jean-Louis (Paris : Centre d'Etudes et de Documentations Pédagogiques Paris British Group of Sexological Research, 1970)
Fonds Suzan Daniel (FSD)
Engels
Monografie